A mobile app for triangulating strategies in phosphate education targeting patients with chronic kidney disease in Malaysia: development, validation, and patient acceptance - Teong, Lee-Fang; Khor, Ban-Hock; Kristo Radion Purba; Abdul Halim Abdul Gafor; Goh, Bak-Leong; Bee, Boon-Cheak; Rosnawati Yahya; Sunita Bavanandan; Ng, Hi-Ming; Sharmela Sahathevan; Sreelakshmi Sankara Narayanan; Zulfitri Azuan Mat Daud; et al. (Multidisciplinary Digital Publishing Institute, 2023)
Hyperphosphatemia afflicts end-stage chronic kidney disease (CKD) patients, contributing to comorbidities and mortality. Management strategies are dialysis, phosphate binder, and limiting dietary phosphate intake, but treatment barriers are poor patient compliance and low health literacy arising from low self-efficacy and lack of educational resources. This study describes developing and validating a phosphate mobile application (PMA). The PMA development based on the seven-stage Precaution Adoption Process Model prioritized titrating dietary phosphate intake with phosphate binder dose supported by educational videography. Experts (n = 13) first evaluated the PMA for knowledgebased accuracy, mobile heuristics, and clinical value. Adult HD patients validated the improved PMA using the seven-point mHealth App Usability Questionnaire (MAUQ). Patient feedback (n = 139) indicated agreement for ease of use (69.2%), interface and satisfaction (69.0%), and usefulness (70.1%), while 72.7% said they would recommend this PMA. The expectation confirmation for 25 PMA features ranged from 92.1% (lifestyle) up to 100.0% (language option); and the utilization rate of each feature varied from 21.6% (goal setting and feature-based log) to 91.4% (information on dietary phosphate and phosphate binder). The Conclusions: MyKidneyDiet-Phosphate Tracker PMA was acceptable to adult Malaysian HD patients as part of clinical phosphate management in low-resource settings.